INFECTION RATE AND CHEMOTHERAPY OF VARIOUS HELMINTHES IN DIARRHOEIC SHEEP IN AND AROUND LAHORE - M. Ijaz; M. S. Khan; M. Avais; K. Ashraf M. M. Ali; M. Z.U. Khan (Journal of Animal and Plant Sciences, 2009)
The present study was carried out to find out the infection rate of gastrointestinal tract helminthiasis and its association with diarrhoea in sheep in Lahore, Pakistan. For this purpose, 300 faecal samples from sheep suffering from diarrhoea presented at the Outdoor Hospital, Department of Clinical Medicine and Surgery (CMS) and various private and government veterinary hospitals located in Lahore were collected and examined coprologically for the presence of helminthes. Overall infection rate of GIT helminthes in sheep was 70.67%. Infection rate of nematodes was higher (50.67%) than trematodes (18.67%) and cestodes (1.34%).The efficacy of albendazole sulphoxide was 67%, 90% and 98% at day 3, 7 and 14, respectively, while the efficacy of albendazole was 47%, 88% and 96% at day 3, 7 and 14, respectively. Lowest efficacy of Garlic powder 8%, 16% and 21% at day 3, 7 and 14, respectively was observed. It may be concluded that albendazole sulphoxide is the most effective drug against these helminthes in sheep.
Keywords: Diarrhoea; Efficacy; Albendazole; Albendazole sulphoxide; Garlic powder